Human resource management: systemic approach in a global perspective - Perea Rivera, José Luis (2006)
The thematic one must like intention to approach the main processes of the management of the human resources in the organizations of production of goods and services (company, industry, institution) is of the public or deprived sector, that in its operational dynamics is present the psychological component. Also it treats his interrelation that under a sistémico approach and in the global perspective towards the modernity of century XXI within the agreement and the organizacional change, serves as support in the systematization of the management; which it causes the consistency between the planning, the evaluation for aims of the continuous improvement, accreditation or certification of quality of his processes,and the pertinencia with the demands of the social reality, economic and also political of the country.